Vegetation und Landesnatur im südlichen Gaoligong Shan (West Yünnan) - Schweinfurth, Ulrich; Weilie, Chen (ERDKUNDE, 1984)
The recent development in which Chinese scientists have spent study periods abroad opens welcome possibilities to hear more about work being done in China before the ’bamboo curtain’ was to some degree lifted in the wake of the Tibet Symposium of 1980 in Beijing. The case under consideration is concerned with field work performed by scientists of the Institutum Botanicum, Academia Sinica, in the southern parts of the Gaoligong Shan, known as the Irrawaddy-Salween Divide. The area commands particular interest being at the southern extremity of the river gorge country and, also, because its vegetation is virtually unknown. During the days of the mainly British plant hunters in the Chinese-Tibetan borderlands the southern Gaoligong Shan respectively, the Irrawaddy-Salween Divide was ’FORREST country’. George Forrest (1873-1932) had developed his very personal method of collecting; he used considerable numbers of assistants, kept no diary and was not given to writing, with the result that it is virtually impossible to know where he has been personally, or where his collectors went. The Chinese team aimed first of all at finding out about the ’actual’ vegetation as well as in due course about the floristic relationship of the southern Gaoligong Shan to the Himalayan system further N. The following types were distinguished: tropical evergreen rainforest; tropical semi-evergreen rain forest; evergreen lower montane forest; evergreen upper montane forest: lower belt: evergreen broadleaved forest, upper belt: Rhododendron-coniferous forest; Sinarundinaria-Rhododendron scrub; dry lower slopes of Salween valley; secondary vegetation: deciduous forest: Alnus nepalensis; coniferous forest: Pinus yunnanensis, Pinus armandi; grassland. After a brief description of the various types, the regional distribution of the vegetation types is discussed dealing with the vertical and horizontal differentiation in the southern Gaoligong Shan. Thereafter the relation to the vegetation types as known from the eastern Himalayas is compared. In conclusion the particular interest the area attracts is emphasized, its mountain ranges providing, on the one hand, temperate habitats as far S as 25°N, and, on the other, offering in its valleys a way for tropical lowland vegetation to penetrate deep into the mountains. This results in an intricate pattern of a three-dimensional interrelationship of the northern and southern, temperate and tropical elements, rendering the area an attractive objective for further field work, where elements of central and peripheral Asia meet.